2020
DOI: 10.2196/21886
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Communication: Creating a Path to COVID-19 Public Health Activism in Adolescents Using Social Media

Abstract: The COVID-19 pandemic and related public health efforts limiting in-person social interactions present unique challenges to adolescents. Social media, which is widely used by adolescents, presents an opportunity to counteract these challenges and promote adolescent health and public health activism. However, public health organizations and officials underuse social media to communicate with adolescents. Using well-established risk communication strategies and insights from adolescent development and human-comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Studies already showed, for example, that adolescents' anxiety and depressive symptoms increased since the outbreak of the COVID-19, especially during homequarantine (e.g., Kılınçel et al, 2020;Magson et al, 2021;Marques de Miranda et al, 2020), as well as their social media use (Paschke et al, 2021). However, researchers have also pointed out the "bright" side of social media use during the pandemic, i.e., the way social networking helped adolescents cope with feelings of loneliness and anxiety during the Covid-19 lockdown (Cauberghe et al, 2021) and engage in public health activism (Sobowale et al, 2020). More importantly, as Spigel and her collaborators suggested (2021), the perceived disruptions in access to care worsened eating disorder symptomatology in youth during the pandemic.…”
mentioning
confidence: 99%
“…Studies already showed, for example, that adolescents' anxiety and depressive symptoms increased since the outbreak of the COVID-19, especially during homequarantine (e.g., Kılınçel et al, 2020;Magson et al, 2021;Marques de Miranda et al, 2020), as well as their social media use (Paschke et al, 2021). However, researchers have also pointed out the "bright" side of social media use during the pandemic, i.e., the way social networking helped adolescents cope with feelings of loneliness and anxiety during the Covid-19 lockdown (Cauberghe et al, 2021) and engage in public health activism (Sobowale et al, 2020). More importantly, as Spigel and her collaborators suggested (2021), the perceived disruptions in access to care worsened eating disorder symptomatology in youth during the pandemic.…”
mentioning
confidence: 99%
“…This is because an overwhelming majority of teenagers use social media; according to a 2018 survey, 71% of Americans aged 13-17 use Instagram alone (Schaeffer, 2021). Recently, organizations such as the Center for Disease Control (CDC), the World Health Organization (WHO), and the United Nations Children's Fund (UNICEF) have created accounts on platforms such as Tiktok, Youtube, and Snapchat for the sole purpose of sharing safety information surrounding COVID-19 with adolescents (Sobowale et al, 2020). Teenagers themselves are well-positioned to promote habits such as physical distancing amongst their peers, as they have gone through similar social isolation in the midst of the COVID-19 pandemic, which notably "aligns with the adolescents' desire to portray themselves in a positive light" (Sobowale et al, 2020, p. 5).…”
Section: Social Media For Communicating With Teenagersmentioning
confidence: 99%
“…Established authorities provide communications during public health events by using consistent patterns; when applied to the SM schema, it helps listeners of all categories differentiate signal (true facts) versus noise (static and misinformation). 25 Using the CERC method, it allows adolescents to have inclusive access to critical information and empowers them to understand facts as they evaluate their application of information in addition to potential participation in educating others, ie, reposting on various channels or discussing with peers. In SM, given its intentionally brief messaging structure, Emergency Management messaging needs to successfully harness the output of a knowledge funnel process (data gathering-information filtering-intelligence content) to give directive insights leading to appropriate decisions.…”
Section: Risk Communication: Best Practice and Application To Adolescentsmentioning
confidence: 99%
“…In SM, given its intentionally brief messaging structure, Emergency Management messaging needs to successfully harness the output of a knowledge funnel process (data gathering-information filtering-intelligence content) to give directive insights leading to appropriate decisions. 25 The six basic principles of CERC as developed by the CDC (including the need to be first, be right, and be credible as well as to express empathy, promotion action, and show respect) all still apply 12 ; through SM, it is now possible to add a seventh aspect "be interactive" to meet SMART objectives 26 for in a more time-sensitive manner for life-critical topics. The interactive nature of SM has shifted the traditional emphasis of CERC from the sender (the Emergency Management agency or, in pandemic, healthcare organization) to the receiver (those experiencing the crisis or risk).…”
Section: Risk Communication: Best Practice and Application To Adolescentsmentioning
confidence: 99%
See 1 more Smart Citation